Geoprocessing applied to physiographic characterization of the Lontras River Basin - Paraná, Brazil | Geoprocessamento aplicado à caracterização fisiográfica da Bacia do Rio Lontras - Paraná, Brasil - Mendes, Isaque de Souza; Mercante, Erivelto; Scariotto, Mônica Carminati; Maggi, Marcio Furlan; Correa, Marcus Metri; Kusminski, Douglas (Revista Geama, 2016)
The morphometric characterization is considered an important tool in the management of river basins, and it provides relevant information to decision making by managers who are associated with the geographic divisions. The use of Geographic Information Systems (GIS) and remote sensing tools, widespread in monitoring and spatial analysis, is characterized as a facilitator component in the search for characterization and identification of factors which influence the geomorphometric parameters of the territory. The current spread of geoprocessing and GIS in general, culminate in a wide availability of storage systems and computer programs for data processing and conversion. Based on the above, this study aimed to morphometric and rainfall characterization of the Salto do Lontra watershed, which covers the municipalities of Salto do Lontra and Nova Esperança do Sudoeste located in West Region of Paraná State, Brazil, using the software Qgis 2.14. In this regard, the Digital Elevation Model (DEM) was used with a spatial resolution of thirty meters, provided by the National Institute for Space Research and historical precipitation data provided by the Paraná Water Institute. Through the MDE an altimetric data correction was performed obtaining a Hydrologically Consistent Digital Elevation Model (HCDEM), in which were obtained by manipulating data in a GIS environment, physical variables to determine the morphometric parameters. The results demonstrated that the Salto do Lontra watershed has a drainage area of 177.54 km² and a perimeter of 99.29 km. The compactness coefficient obtained was 2.09, the form factor 0.19 and circularity index 0.23, indicating that the basin has elongated shape and low propensity to flooding. The drainage density was 0.85 km.(km²)-1, time of concentration 535.59 min. and sinuosity index of 40.57%. In addition, the data obtained in this study indicated that the average annual precipitation was 1896.85 mm, watching orographic effect on its distribution.